Pathogenesis, Diagnosis, and Examination of Corynebacterium diphtheriae - Ningsih, Ika; Safrullah, Muhammad Iqbal (UI Scholars Hub, 2025)
Corynebacterium diphtheriae is a rod-shaped bacterium, Gram-positive (purple), growth requires the presence of oxygen or can live with oxygen or without oxygen, nonmotile, non-capsular, non-sporing, catalase positive. Most species ferment carbohydrates such as fructose, galactose, glucose, maltose, and mannose and produce an exotoxin called diphtheria toxin (DT) which can cause diphtheria, a respiratory infection characterized by sore throat and the production of a thick layer / gray pseudomembrane and generally affects children aged 15 years and under and is very vulnerable in people who are not immunized and in low immune systems. Diphtheria is a dangerous and life-threatening disease if not detected early, so clinical diagnosis must be made immediately. Therefore, clinical diagnosis methods must be supported by laboratory examinations to detect the bacteria. Examinations that can be performed for the diagnosis of bacteria of the genus Corynebacterium include culture examination on growth media, toxicity test/toxin identification, serology test, histology examination and imaging test, biomarker test, and PCR (Polymerase Chain-Reaction) test.